The total costs of corporate borrowing in the loan market: Don't ignore the fees - Tobias Berg; Anthony Saunders; Sascha Steffen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
More than 80% of US syndicated loans contain at least one fee type and contracts typically specify a menu of spread and different types of fees. We test the predictions of existing theories about the main purposes of fees and provide supporting evidence that: (1) fees are used to Price options embedded in loan contracts such as the draw-down option for credit lines and the cancellation option in term loans; and (2) fees are used to screen borrowers about the likelihood of exercising these options. We also propose a new total-cost-of-borrowing measure that includes various fees charged by lenders.
Keywords: 330